Long-term efficacy of leptin replacement in patients with Dunnigan-type familial partial lipodystrophy - Park, Jean Y. (2007)
The Dunnigan-type familial partial lipodystrophy (FPLD) is characterized by a variable loss of fat from the extremities and trunk and excess subcutaneous fat in the chin and supraclavicular area. Associated metabolic abnormalities include hypoleptinemia, insulin resistance, and dyslipidemia. Our goal was to observe changes in metabolic parameters for patients with FPLD on long-term leptin replacement and to compare the metabolic characteristics seen in FPLD with those seen in generalized lipodystrophy (GL) from our previous studies. This was an open-label study of 6 patients with FPLD receiving maximal doses of oral antidiabetic and lipid-lowering medications at baseline. Recombinant leptin was given through twice-daily subcutaneous injections at a maximal dose of 0.08 mg/kg per day over 12 months to simulate normal to high normal physiologic levels. Triglycerides were reduced by 65% at 4 months (749 ± 331 to 260 ± 58 mg/dL) and significantly reduced at 12 months for 5 patients (433 ± 125 to 247 ± 69 mg/dL; P = .03). Total cholesterol also decreased (280 ± 49 to 231 ± 41 mg/dL; P = .01). Insulin sensitivity and fasting glucose levels (190 ± 26 to 151 ± 15 mg/dL; P < .01) improved. Glucose tolerance and glycosylated hemoglobin levels (8.4% ± 0.6% to 8.0% ± 0.4%; P = .07) did not change. As shown in patients with GL, patients with FPLD have improvement in triglycerides, fasting glucose, and insulin sensitivity with leptin replacement. In contrast to the patients with GL, the patients with FPLD are older, have higher leptin levels, and notably lower insulin secretion for a similar degree of hyperglycemia. Low-dose recombinant methionyl human leptin for patients with FPLD has an important role in improving triglycerides, beyond that of available lipid-lowering agents. In improving glycemic control, normalization of glucose tolerance in hypoinsulinemic patients with FPLD requires insulin and leptin therapy. This is the first study to examine the effects of long-term leptin replacement in patients with FPLD.